Rancang Bangun dan Pengujian Pemasak Surya yang Sesuai untuk Kondisi Indonesia; Studi Kasus Kota Medan - HImsar Ambarita (Jurnal Dinamis, 2013)
AbstractThe most abundant renewable energy source is solar energy which is available ineverywhere. In Indonesia, the potency is estimated of 4.8 kWh/m2/day or 17.28 MJ/m2/day. InMedan city a potency of 3.54 kWh/m2/day has been measured. On of the most promisingapplication for solar energy resource is cooking. As known, in developing countries, it is believedthat cooking is the most consuming energy. Research and development on a solar cooker can beconsider as a solution. Here a simple direct box type solar cooker has been designed andfabricated. The solar cooker was tested by exposing to solar radiation in Medan city, thecoordinate of the tested spot is 3o35' North and 98o40' East. The main dimensions of the solarcooker are: absorber of 83.5 cm × 83.5 cm and 29.5 cm of height. The load here is water whichwas varied from 3 kg, 5 kg and 6 kg. Temperatures, radiation, RH, and wind speed wererecorded with an interval of 1 minute. The results show that temperatures of the absorber can beover of 120oC. Thus it can be used to boil water up to 6 kg. The thermal efficiency of the presentsolar cooker is about 20.53. It is suggested to optimize this solar cooker by testing it as a solarrice cooker and coupling with thermal storage. The main conclusion is that it is possible todevelop simple solar cooker in Indonesian climate.Keywords: Solar Energi, Solar Cooker, Direct System